Phenolic profile, α-amylase inhibition and molecular docking scrutiny of the trunk bark of Pinus pinea growing in Tunisia. (4th March 2023) - Ben Mustapha, Mayssa; Lazrag, Houda; Khemis, Eya; Kaplan, Muammer; Goren, Ahmet Ceyhan; Harrath, Abdel Halim; Ben Jannet, Hichem
Abstract: The phenolic profile of ethyl acetate and methanol extracts from the trunk bark of Pinus pinea growing in Tunisia was determined using Liquid Chromatography coupled to High Resolution Mass Spectrometry (LC-HRMS) method and their anti-α-amylase potential and the mode of inhibition were determined in a kinetic study. Methanol extract was found to be richer in phenolics. Eighteen constituents were identified in ethyl acetate extract with trans -taxifolin (7.57 g/kg), as the main compound. Eighteen compounds were detected in methanol extract with ellagic acid (88.06 g/kg), as the major constituent. Ethyl acetate and methanol extracts inhibited α-amylase with half-maximal inhibitory concentration (IC50 ) values of 9.16 and 8.33 μg/mL, respectively. The ethyl acetate and methanol extracts exerted a non-competitive and a competitive inhibition on α-amylase enzyme, respectively. This activity was supported by molecular docking analysis of some major compounds of both extracts. All these compounds showed a low binding energy and they could bind with the key residues including ASP-206 and GLU-230 of the α-amylase enzyme and these ligands were also surrounded by other active site residues. These findings suggest that P. pinea extracts could serve as safe and efficient α-amylase inhibitors to treat postprandial hyperglycemia in diabetic patients.